2017
DOI: 10.1007/s12298-017-0490-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of pesticides mancozeb and chlorpyrifos: correlation with the antioxidative defence system in Allium cepa

Abstract: Pesticides are a group of chemical substances which are widely used to improve agricultural production. However, these substances could be persistent in soil and water, accumulative in sediment or bio-accumulative in biota depending on their solubility, leading to different types of environmental pollution. The present study was done to assess the impact of pesticides-mancozeb and chlorpyrifos, via morphological and physiological parameters using test system. Phytotoxic effects of pesticides were examined via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 45 publications
5
15
0
1
Order By: Relevance
“…The lowest concentration of these compounds (100 µmol L −1 ) stimulated root elongation but higher doses inhibited it, albeit marginally when compared to the herbicide S ‐metolachlor. Elongation tests with the insecticides Chlorpyrifos, α‐cypermethrin and λ‐cyhalothrin in onion and tomato presented a similar pattern (growth stimulation at lower concentrations and inhibition at higher) . Higher adverse effects of insecticidal molecules on root growth compared to shoot elongation, as observed in this study, have been reported for cypermethrin elsewhere …”
Section: Discussionsupporting
confidence: 84%
“…The lowest concentration of these compounds (100 µmol L −1 ) stimulated root elongation but higher doses inhibited it, albeit marginally when compared to the herbicide S ‐metolachlor. Elongation tests with the insecticides Chlorpyrifos, α‐cypermethrin and λ‐cyhalothrin in onion and tomato presented a similar pattern (growth stimulation at lower concentrations and inhibition at higher) . Higher adverse effects of insecticidal molecules on root growth compared to shoot elongation, as observed in this study, have been reported for cypermethrin elsewhere …”
Section: Discussionsupporting
confidence: 84%
“…Mancozeb and metalaxyl were often in use among small-scale farmers growing tomatoes, least among small-scale farmers growing kales. The results agree with those of Fatma, et al (2018) who noted that mancozeb and chlorpyrifos have been proved to be effective in the reproduction in large scale system including and not limited to increasing vegetable production and these pesticides have recorded environmental persistence are highly toxic towards aquatic ecosystem including fish. De Silva et al (2010) add that these pesticides are also toxic to pollinators such as bees and have been associated with reduced bee populations.…”
Section: Effects Of Misuse Of Agrochemicalssupporting
confidence: 91%
“…Further, it increased the antioxidant enzyme activities including CAT, POX and GR in tomato seedlings (Yüzbaşıoğlu & Dalyan 2019). Another study has indicated that mancozeb and chlorpyrifos increased CAT and POD activities in A. cepa seedling in a time and concentration-dependent manner (Fatma et al 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Another study has indicated that mancozeb and chlorpyrifos increased CAT and POD activities in A. cepa seedling in a time and concentration-dependent manner (Fatma et al 2018).…”
Section: Discussionmentioning
confidence: 97%